Acid and alkali resistant positively charged composite nanofiltration membrane as well as preparation method and application thereof
By introducing chemically inert groups and quaternary ammonium salt structures into the acid-base-resistant separation layer of the nanofiltration membrane, the existing nanofiltration membrane has poor tolerance and low retention performance under acidic conditions, and the effect of efficient removal of divalent and high-valent metal cations in an acid/alkaline environment is achieved.
Patent Information
- Application Number
- CN202311142013.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-05
AI Technical Summary
The existing polyamide nanofiltration membranes have poor tolerance under acidic conditions, resulting in a decrease in retention performance and low removal rate of divalent and high-valent metal cations, which cannot meet the needs of acidic wastewater treatment of titanium dioxide.
A acid-base-resistant positive-charge composite nanofiltration membrane was developed. By introducing chemically inert groups and quaternary ammonium salt structures into the acid-base-resistant separation layer of the nanofiltration membrane, the acid/base tolerance of the membrane and the retention ability of divalent and high-valent metal cations were improved.
It achieves a high water flux and excellent interception effect under an acid/alkaline environment, has good interception ability for divalent and high-valent metal cations, and can realize the recycling of acid.
Smart Images

Figure CN119565396A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the membrane field, and in particular to an acid-base resistant positively charged composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] The main component of titanium dioxide is titanium dioxide, which is safe and non-toxic. It is widely used in industrial fields such as coatings, papermaking, printing, chemical fiber, plastics, rubber, etc., of which coatings account for more than 60%. my country is a major producer of titanium dioxide. Since 2019, the overall scale of titanium dioxide in my country has ranked first in the world. Among them, the output of titanium dioxide produced by the sulfuric acid method accounts for more than 90% of the total output of titanium dioxide. In the process of producing titanium dioxide by the sulfuric acid method, for every ton of titanium dioxide produced, 8-10 tons of waste sulfuric acid with a concentration of 15-20wt% will be produced. The above waste sulfuric acid solution contains about 5wt% of Fe 2+ , and a small amount of metal sulfates such as aluminum, manganese, calcium, and magnesium. How to solve the low-cost treatment and pollution-free discharge of sulfuric acid titanium dioxide acid wastewater is the primary problem that plagues the development of my country's titanium dioxide industry.
[0003] At present, domestic titanium dioxide enterprises mainly adopt three processes for comprehensive treatment of waste acid: neutralization, waste acid concentration, and purification. Among them, the alkali neutralization method is the most commonly used waste acid treatment process, but this process not only cannot separate and recover sulfuric acid and many valuable metals in the waste acid, but also produces titanium gypsum and other solid wastes with calcium sulfate as the main component. The treatment of these solid wastes has become a new problem. With the development of membrane separation technology, nanofiltration provides a new option for the treatment of titanium dioxide acidic wastewater. Based on size screening and Donnan effect, nanofiltration membrane can selectively separate monovalent and divalent ions, and has good application prospects in the above process. In addition, the membrane treatment process is short, simple to operate, and has low production costs. While treating waste acid, it can also achieve the recycling of sulfur resources, which is of great significance to the green and sustainable development of the titanium dioxide industry.
[0004] The problem is that the commercial polyamide nanofiltration membrane is not acid-resistant. Under acidic conditions, the C=O bond in the polyamide structure is easily affected by H + The nucleophilic electrons attack the amide bonds, causing hydrolysis of the amide bonds, which destroys the membrane separation layer structure and significantly reduces the retention performance. In addition, the acyl chloride groups on the surface of the polyamide membrane hydrolyze to form a large number of carboxyl groups, making the membrane surface negatively charged. Due to the Donnan effect, the membrane is less sensitive to Fe 2+ , Ca 2+ Mg 2+ The removal rate of divalent cations is low. In comparison, positively charged nanofiltration membranes better meet the needs of the above application scenarios.
[0005] Therefore, there is an urgent need to develop a positively charged nanofiltration membrane with a simple preparation method and excellent acid resistance. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of poor acid / alkali tolerance and low interception rate of divalent and high-valent metals in the existing nanofiltration membrane, and to provide an acid-alkali resistant positively charged composite nanofiltration membrane and a preparation method and application thereof. The acid-alkali resistant positively charged composite nanofiltration membrane has an acid-alkali resistant separation layer comprising chemically inert groups, so that the nanofiltration membrane can also be used in an acid / alkaline environment; the acid-alkali resistant separation layer also comprises a quaternary ammonium salt structure, so that the nanofiltration membrane has excellent interception capacity for divalent and high-valent metal cations while maintaining a relatively high water flux, and can achieve the concentration of divalent and high-valent metal cations and the recovery and utilization of acids.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides an acid-base resistant positively charged composite nanofiltration membrane, wherein the acid-base resistant positively charged composite nanofiltration membrane comprises a bottom layer, a porous support layer and an acid-base resistant separation layer stacked in sequence;
[0008] Wherein, the acid-base resistant separation layer contains a quaternary ammonium salt structure.
[0009] The second aspect of the present invention provides a method for preparing an acid- and alkali-resistant positively charged composite nanofiltration membrane, wherein the preparation method comprises the following steps:
[0010] S1, preparing a porous supporting layer on the bottom layer;
[0011] S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase containing a polyamine having a tertiary amine group, and is second contacted with an organic phase containing a polyamine having a polar monomer, and after heat treatment, a composite nanofiltration membrane including an acid-base resistant separation layer is obtained;
[0012] S3, bringing the composite nanofiltration membrane into a third contact with an organic solution containing halogenated alkanes and a catalyst, and drying to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane.
[0013] The third aspect of the present invention provides an acid-base resistant positively charged composite nanofiltration membrane prepared by the aforementioned preparation method.
[0014] A fourth aspect of the present invention provides an application of the aforementioned acid- and alkali-resistant positively charged composite nanofiltration membrane in the field of water treatment.
[0015] Through the above technical scheme, the acid-base resistant positively charged composite nanofiltration membrane provided by the present invention and its preparation method and application obtain the following beneficial effects:
[0016] The acid-base resistant separation layer of the acid-base resistant positively charged composite nanofiltration membrane provided by the present invention has chemically inert groups, which improves the acid / base tolerance of the acid-base resistant positively charged composite nanofiltration membrane; the acid-base resistant separation layer has quaternary ammonium salt groups, which increases the positive charge density on the surface of the composite nanofiltration membrane, so that the acid-base resistant positively charged composite nanofiltration membrane has a good retention effect on divalent and high-valent metal cations, and at the same time can also enable the acid-base resistant positively charged composite nanofiltration membrane to maintain a higher water flux.
[0017] In the preparation method of the acid- and alkali-resistant positively charged composite nanofiltration membrane provided by the present invention, halogenated alkanes react biochemically with tertiary amines in the acid- and alkali-resistant separation layer under the action of an alkaline catalyst to convert the tertiary amines into quaternary ammonium salt groups with positive charges. The retention capacity of the nanofiltration membrane for divalent and high-valent metal cations is improved through the repulsive effect between the positive charges, and at the same time, the acid- and alkali-resistant positively charged composite nanofiltration membrane can maintain a relatively high water flux. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the XPS spectrum of the surface nitrogen atoms of the acid-base resistant positively charged composite nanofiltration membrane of Example 1 of the present invention. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The first aspect of the present invention provides an acid-base resistant positively charged composite nanofiltration membrane, wherein the acid-base resistant positively charged composite nanofiltration membrane comprises a bottom layer, a porous support layer and an acid-base resistant separation layer stacked in sequence;
[0021] Wherein, the acid-base resistant separation layer contains a quaternary ammonium salt structure.
[0022] In the present invention, the acid-base resistant separation layer of the acid-base resistant positively charged composite nanofiltration membrane contains a quaternary ammonium salt structure, which significantly improves the positive charge density on the surface of the acid-base resistant positively charged composite nanofiltration membrane, and the repulsion effect brought about by the positive charges improves the retention effect of the acid-base resistant positively charged composite nanofiltration membrane on divalent iron ions, thereby maintaining the high water flux of the acid-base resistant positively charged composite nanofiltration membrane while improving the retention capacity of the acid-base resistant positively charged composite nanofiltration membrane for divalent and high-valent metal cations.
[0023] According to the present invention, the quaternary ammonium salt structure comprises the structural formula shown in Formula I and / or the structural formula shown in Formula II,
[0024]
[0025] X is a halogen; n is an integer of 0-10; and m is an integer of 2-10.
[0026] In the present invention, * refers to the bonding position where the quaternary ammonium salt structure is connected to the acid-base resistant separation layer.
[0027] Furthermore, X is Cl, Br or I.
[0028] Furthermore, n is an integer of 0-7; m is an integer of 2-8.
[0029] According to the present invention, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer.
[0030] In the present invention, a specific acid-base resistant separation layer introduces inert chemical groups into the composite nanofiltration membrane, thereby improving the stability of the composite nanofiltration membrane, enabling the composite nanofiltration membrane of the present invention to be used in acid / alkaline environments, thereby expanding the scope of use.
[0031] Furthermore, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.
[0032] According to the present invention, the content of nitrogen atoms in the quaternary ammonium salt groups in the acid- and alkali-resistant positively charged composite nanofiltration membrane is 0.5-5 at.%.
[0033] In the present invention, when the content of nitrogen atoms in the quaternary ammonium salt structure meets the above range, it indicates that the acid-base resistant positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups, which can make the composite nanofiltration membrane have a higher surface positive potential.
[0034] Furthermore, the content of nitrogen atoms in the quaternary ammonium salt groups in the acid- and alkali-resistant positively charged composite nanofiltration membrane is 2-5 at.%.
[0035] In the present invention, the surface Zeta potential of the nanofiltration membrane refers to the surface Zeta potential at pH=7.
[0036] According to the present invention, the surface Zeta potential of the acid-base resistant positively charged composite nanofiltration membrane is 0-30 mV.
[0037] In the present invention, when the surface Zeta potential of the acid- and alkali-resistant positively charged composite nanofiltration membrane satisfies the above range, it indicates that the composite nanofiltration membrane has a high surface electrode potential. When it is used for the separation of divalent and high-valent metal cations, it can better repel metal cations, making it difficult for metal cations in the liquid to pass through the separation membrane, thereby obtaining a higher retention capacity for divalent and high-valent metal cations.
[0038] Furthermore, the surface Zeta potential of the acid- and alkali-resistant positively charged composite nanofiltration membrane is 5-20 mV.
[0039] According to the present invention, the average pore size of the acid-base resistant positively charged composite nanofiltration membrane is 0.1-0.5 nm.
[0040] In the present invention, the average pore size of the acid-base resistant positively charged composite nanofiltration membrane is tested by using the PEG solute transfer method.
[0041] In the present invention, when the average pore size of the nanofiltration membrane meets the above range, the acid-base resistant positively charged composite nanofiltration membrane has a high density, can better exclude divalent and high-valent metal cations, so that the divalent and high-valent metal cations in the liquid are not easy to pass through the separation membrane, thereby obtaining a higher retention capacity for divalent and high-valent metal cations.
[0042] Furthermore, the average pore size of the acid-base resistant positively charged composite nanofiltration membrane is 0.15-0.3 nm.
[0043] According to the present invention, the contact angle of the acid-base resistant positively charged composite nanofiltration membrane is 20°-80°.
[0044] In the present invention, when the contact angle of the nanofiltration membrane meets the above range, it indicates that the surface of the acid-base resistant positively charged composite nanofiltration membrane has good hydrophilicity, thereby obtaining a higher water flux.
[0045] Furthermore, the contact angle of the acid-base resistant positively charged composite nanofiltration membrane is 30°-60°.
[0046] In the present invention, the bottom layer and the porous support layer are not specifically limited, and can be made of various existing materials that have a certain strength and can be used for nanofiltration and reverse osmosis membranes.
[0047] In the present invention, the bottom layer is a non-woven fabric material, preferably polyester and / or polyethylene.
[0048] In the present invention, the porous support layer material may be at least one of polyethersulfone, polysulfone, polyarylether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride and polyaryletherketone.
[0049] According to the present invention, the present invention does not particularly limit the thickness of the bottom layer, the porous support layer, and the acid-base resistant separation layer, which can be a conventional choice in the field, but in order to enable the three layers to play a better synergistic role, so that the obtained composite nanofiltration membrane can better have excellent retention capacity for divalent and high-valent metal cations and higher water flux, preferably, the thickness of the bottom layer is 30-150μm, preferably 50-120μm; the thickness of the porous support layer is 10-100μm, preferably 30-60μm; the thickness of the acid-base resistant separation layer is 10-500nm, preferably 50-300nm.
[0050] In a particularly preferred embodiment, the thickness of the acid-base resistant separation layer is 120-180 nm.
[0051] The second aspect of the present invention provides a method for preparing an acid- and alkali-resistant positively charged composite nanofiltration membrane, wherein the preparation method comprises the following steps:
[0052] S1, preparing a porous supporting layer on the bottom layer;
[0053] S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase containing a polyamine having a tertiary amine group, and is second contacted with an organic phase containing a polyamine having a polar monomer, and after heat treatment, a composite nanofiltration membrane including an acid-base resistant separation layer is obtained;
[0054] S3, bringing the composite nanofiltration membrane into a third contact with an organic solution containing halogenated alkanes and a catalyst, and drying to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane.
[0055] In the present invention, the composite nanofiltration membrane is contacted with an organic solution containing halogenated alkanes and a catalyst. The halogenated alkanes react biochemically with the tertiary amine in the acid- and alkali-resistant separation layer under the action of the catalyst, and the tertiary amine is converted into a quaternary ammonium salt group with a positive charge. The retention capacity of the acid- and alkali-resistant positively charged composite nanofiltration membrane for divalent and high-valent metal cations is improved through the repulsive effect between the positive charges, and at the same time, the acid- and alkali-resistant positively charged composite nanofiltration membrane can maintain a higher water flux.
[0056] In the present invention, there is no particular limitation on the method for preparing the porous supporting layer on the bottom layer. It can be prepared by conventional methods in the art, preferably by a phase inversion method. Specifically, a polymer solution of the porous supporting layer material is coated on one surface of the bottom layer, and the porous supporting layer is obtained by phase inversion.
[0057] In the present invention, the phase inversion method can preferably be: dissolving the supporting layer polymer material in a solvent to obtain a polymer solution with a concentration of 10-20 weight %, and degassing at 20-40°C for 10-180min; then coating the polymer solution on the bottom layer to obtain an initial membrane, and then soaking it in water at a temperature of 10-30°C for 10-60min to obtain the supporting layer polymer porous membrane through the phase inversion layer.
[0058] The solvent may be N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, or the like.
[0059] According to the present invention, in step S2, the polyamine containing a tertiary amine group is selected from at least one of polyethyleneimine, polyethylenepolyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazinediethylamine and 1,4-bisaminopropylpiperazine, preferably polyethyleneimine and / or polyethylenepolyamine.
[0060] According to the present invention, in the aqueous phase of the polyamine containing tertiary amine groups, the concentration of the polyamine containing tertiary amine groups is 0.1 wt%-10 wt%, preferably 0.5 wt%-2.5 wt%.
[0061] According to the present invention, the polyvalent polar monomer is selected from at least one of polyvalent isocyanates, triazine compounds containing at least two C-Cl bonds, and polyvalent sulfonyl chlorides.
[0062] According to the present invention, the polyisocyanate is selected from at least one of meta-phenylenediisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylenediisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylenediisocyanate, 3,3'-dichloro-4,4'-diisocyanatebiphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl meta-phenylenediisocyanate; preferably selected from 1,4-phenylenediisocyanate and / or 1,3-phenylenediisocyanate.
[0063] According to the present invention, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine; preferably cyanuric chloride.
[0064] According to the present invention, the polysulfonyl chloride is selected from at least one of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalene disulfonyl chloride, 1,3-naphthalene disulfonyl chloride, 2,7-naphthalene disulfonyl chloride, 1,3,5-benzene trisulfonyl chloride and 1,3,6-naphthalene trisulfonyl chloride; preferably 1,3-benzenedisulfonyl chloride.
[0065] According to the present invention, in the organic phase, the concentration of the multi-polar monomer is 0.01 wt%-2 wt%, preferably 0.05-1 wt%.
[0066] According to the present invention, the amount of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing multiple polar monomers is such that the weight ratio of the polyamine containing tertiary amine groups to the multiple polar monomers is 2-200:1.
[0067] In the present invention, when the weight ratio of the polyamine containing tertiary amine groups to the polypolar monomers is controlled to meet the above range, sufficient interfacial polymerization reaction between the polyamine containing tertiary amine groups and the polypolar monomers can be ensured, thereby improving the crosslinking density of the obtained acid-base resistant separation layer.
[0068] Furthermore, the amounts of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing the multi-polar monomers are such that the weight ratio of the polyamine containing tertiary amine groups to the multi-polar monomers is 5-80:1.
[0069] In the present invention, there is no particular limitation on the type of solvent in the organic phase containing the multi-polar monomer, as long as it can dissolve the multi-polar monomer. Preferably, the solvent of the organic phase is one or more of n-hexane, dodecane, n-heptane, and alkane solvent oil (Isopar E, Isopar G, Isopar H, Isopar L, and Isopar M).
[0070] According to the present invention, there is no special limitation on the interfacial polymerization conditions of the polyamine containing tertiary amine groups and the polyvalent polar monomers, and the interfacial polymerization can be carried out according to the conventional conditions in the art. However, in order to enable the three layers to play a better synergistic role and enable the obtained composite nanofiltration membrane to better have excellent retention capacity for divalent and high-valent metal cations and higher water flux, preferably, the first contact time is 5-100s, preferably 10-60s; the second contact time is 10-200s, preferably 20-120s; the heat treatment conditions include: the heat treatment temperature is 40-150°C, preferably 50-120°C; the heat treatment time is 0.5-10min, preferably 1-5min.
[0071] In the present invention, in step S2, the ratio of the volume of the aqueous phase solution of the polyamine containing tertiary amine groups to the membrane area of the membrane layer obtained in step S1 is 0.05-1 mL / cm 2 , preferably 0.1-0.5 mL / cm 2 .
[0072] In the present invention, in step S2, the ratio of the volume of the organic phase solution containing the multi-polar monomer to the membrane area of the membrane layer obtained in step S1 is 0.25-0.5 mL / cm 2 , preferably 0.05-0.3 mL / cm 2 .
[0073] According to the present invention, in step S3, the halogenated alkane is selected from the halogenated alkane represented by formula III and / or the halogenated alkane represented by formula IV;
[0074]
[0075] X1, X2 and X3 are each independently halogen; n is an integer of 0-10; and m is an integer of 2-10.
[0076] The use of the halogenated alkane having the above-mentioned specific structure can further increase the positive charge density on the surface of the positively charged composite nanofiltration membrane and further reduce the average pore size of the nanofiltration membrane.
[0077] Furthermore, X1, X2 and X3 are each independently Cl, Br or I.
[0078] Furthermore, n is an integer of 0-7; m is an integer of 2-8.
[0079] According to the present invention, the halogenated alkane is selected from methyl iodide, ethyl iodide, propyl iodide, butyl iodide, pentyl iodide, hexyl iodide, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, cyclooctane iodide, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, 1,7-diiodoheptane, 1,8-diiodooctane, methyl chloride, ethyl chloride, propyl chloride, butyl chloride, pentyl chloride, hexyl chloride, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, 1,7-diiodoheptane, 1,8-diiodooctane, - at least one of dichloroethane, 1,3-dichloropropane, 1,4-dichlorobutane, 1,5-dichloropentane, 1,6-dichlorohexane, 1,7-dichloroheptane, 1,8-dichlorooctane, methyl bromide, ethyl bromide, propyl bromide, butyl bromide, pentane bromide, hexane bromide, heptane bromide, octane bromide, nonane bromide, cyclopropane bromide, cyclobutane bromide, cyclopentane bromide, cycloheptane bromide, cyclooctane bromide, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, 1,6-dibromohexane, 1,7-dibromoheptane and 1,8-dibromooctane, preferably at least one selected from ethyl bromide, propyl chloride and methyl iodide.
[0080] In the present invention, in order to ensure that the halogenated alkane can react with the tertiary amine group remaining in the acid-base resistant separation layer, the catalyst is an alkaline catalyst. Further, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, potassium tert-butoxide and sodium tert-butoxide, preferably selected from sodium hydroxide and / or sodium tert-butoxide.
[0081] According to the present invention, the organic solution is an alcohol solvent. There is no particular limitation on the specific type of the alcohol solvent, for example, it can be one of methanol, ethanol, n-butanol and isopropanol, preferably methanol or ethanol.
[0082] According to the present invention, in step S3, the concentration of the halogenated alkane in the organic solution is 1 wt%-20 wt%.
[0083] In the present invention, when the concentration of the halogenated alkane in the organic solution in step S3 is controlled to meet the above range, it can ensure that the halogenated alkane is in full contact with the acid-base resistant separation layer in the composite nanofiltration membrane, so that the tertiary amine groups remaining on the surface of the acid-base resistant separation layer can fully react with the halogenated alkane with high reaction efficiency, and finally the surface of the obtained acid-base resistant positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups.
[0084] Furthermore, in step S3, the concentration of the halogenated alkane in the organic solution is 5wt%-10wt%.
[0085] According to the present invention, the concentration of the catalyst is 0.01 wt%-5 wt%.
[0086] In the present invention, when the concentration of the catalyst meets the above range, the halogenated alkane can react more fully with the tertiary amine group on the surface of the composite nanofiltration membrane, introducing a specific content of quaternary ammonium salt groups without wasting the catalyst, thereby improving economic benefits.
[0087] Furthermore, the concentration of the catalyst is 0.1wt%-1wt%.
[0088] According to the present invention, the weight ratio of the halogenated alkane to the catalyst is 2-50:1.
[0089] Furthermore, the weight ratio of the halogenated alkane to the catalyst is 5-30:1.
[0090] According to the present invention, the ratio of the volume of the organic solution to the membrane area of the composite nanofiltration membrane is 0.1-1 mL / cm 2 .
[0091] In the present invention, by controlling the volume of the organic solution and the membrane area of the composite nanofiltration membrane to meet the above-mentioned range, it is possible to ensure that the halogenated alkanes are in full contact with the acid- and alkali-resistant separation layer in the composite nanofiltration membrane, and to ensure that the halogenated alkanes can have a high reaction efficiency with the tertiary amine groups in the acid- and alkali-resistant separation layer, so that the surface of the obtained acid- and alkali-resistant positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups.
[0092] Furthermore, the ratio of the volume of the organic solution to the membrane area of the composite nanofiltration membrane is 0.3-0.5 mL / cm 2 .
[0093] According to the present invention, the conditions of the third contact include: the third contact time is 1-120 minutes.
[0094] In the present invention, when the contact time between the composite nanofiltration membrane and the organic solution containing halogenated alkanes and a catalyst is controlled to meet the above range, it can ensure that the halogenated alkanes fully react with the tertiary amine groups remaining on the surface of the acid-base resistant separation layer, so that the surface of the obtained positively charged composite nanofiltration membrane contains more quaternary ammonium salt groups.
[0095] Furthermore, the conditions of the third contact include: the third contact time is 5-60 minutes.
[0096] In the present invention, the temperatures for the first contact, the second contact and the third contact are not particularly limited, and may be, for example, room temperature (20-30° C.).
[0097] According to the present invention, the drying conditions include: drying temperature of 30-80° C.; drying time of 0.5-5 min.
[0098] Furthermore, the drying conditions include: drying temperature of 40-60° C.; drying time of 1-3 min.
[0099] The third aspect of the present invention provides an acid-base resistant positively charged composite nanofiltration membrane prepared by the aforementioned preparation method.
[0100] A fourth aspect of the present invention provides an application of the aforementioned acid- and alkali-resistant positively charged composite nanofiltration membrane in the field of water treatment and separation.
[0101] In the present invention, the Fe 2+ Retention rate ≥ 90%, preferably ≥ 93%; H + The transmittance is 84-93%, preferably 88-91%, and the water flux is ≥20LMH, preferably ≥22LMH.
[0102] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0103] The present invention will be described in detail below by way of examples. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0104] In the following examples and comparative examples:
[0105] (1) The water flux of the acid- and alkali-resistant positively charged composite nanofiltration membrane was tested by the following method: the nanofiltration membrane was placed in a membrane pool and pre-pressed at 1.5 MPa for 1 h, and then the water permeation of the composite nanofiltration membrane was measured at a pressure of 2 MPa and a temperature of 25°C within a certain period of time, and the water flux was calculated by the following formula:
[0106] J = Q / (A·t), where J is the water flux, Q is the water permeation (L), and A is the effective membrane area of the composite nanofiltration membrane (m 2 ), t is time (h).
[0107] (2) Acid and alkali resistant positively charged composite nanofiltration membrane for divalent Fe 2+ The retention rate and H + The permeability was obtained by the following method: the composite nanofiltration membrane was placed in the membrane pool, the original aqueous solution was a mixed solution of 0.2wt% FeSO4 and 5% H2SO4, and pre-pressed at 1.5MPa for 1h, and then tested at a pressure of 2MPa and a temperature of 25℃. The Fe content in the original aqueous solution and the permeate after 1h was tested. 2+ and H + The membrane is resistant to divalent Fe 2+ The interception rate is R = (C f -Cp ) / C f × 100%, where R is the interception rate, C f is the Fe in the original aqueous solution 2+ The concentration, C p Fe in the permeate 2+ The concentration of H + The transmittance is T = C p ' / C f '×100%, where C p ' is H in the permeate + The concentration, C f ' is the H in the original aqueous solution + concentration.
[0108] (3) The nitrogen atom content in the quaternary ammonium salt structure in the acid- and alkali-resistant positively charged composite nanofiltration membrane is measured by the following method:
[0109] Before the measurement, the nanofiltration membrane was dried in an oven to constant weight, and the elemental composition on the surface of the nanofiltration membrane was determined using a SigmaProbe X-ray photoelectron spectrometer produced by Thermo VG, UK. The content of nitrogen atoms in the quaternary ammonium salt structure in the acid-base resistant separation layer was calculated using the following formula:
[0110]
[0111] Among them, A N + Represents the peak area of nitrogen atoms in the quaternary ammonium salt group in the XPS spectrum ( Figure 1 The peak area at the middle bond energy of 403 eV); A N represents the peak area of nitrogen atoms in the separation layer in the XPS spectrum ( Figure 1 The sum of the peak areas at 403eV and 399eV in N It represents the atomic content (at.%) of nitrogen atoms in the quaternary ammonium salt group in the acid- and alkali-resistant positively charged composite nanofiltration membrane.
[0112] (4) Average pore size test of acid-base resistant positively charged composite nanofiltration membrane: measured by PEG solute transfer method, the detailed steps are as follows:
[0113] (i) Testing the retention rate of nanofiltration membranes for PEG with different molecular sizes;
[0114] (ii) Linear fitting was performed between PEG size and retention rate in a logarithmic-probability coordinate system, and the PEG size corresponding to 50% retention rate was the average pore size of the separation membrane.
[0115] (5) Surface Zeta potential test of acid- and alkali-resistant positively charged composite nanofiltration membrane: The test was performed using a Surpass electrokinetic analyzer (Anton Paar), the circulating fluid was a dilute aqueous solution of KCl, and the pH of the test fluid was 7.
[0116] (6) The contact angle of the acid- and alkali-resistant positively charged composite nanofiltration membrane was tested using the DSA100 surface contact angle measuring instrument produced by KRUSS, Germany, using the static drop method. Before the test, the sample was dried in a 60°C vacuum oven for 30 min to remove surface and internal moisture, and then the dried membrane was attached to a flat glass slide with double-sided tape. The volume of each water drop during the test was 2 μL. The water drop was dropped on the membrane surface for 3 seconds and then tested immediately. After multiple measurements, the average value was taken to determine the final contact angle.
[0117] (7) The thickness of each layer in the acid- and alkali-resistant positively charged composite nanofiltration membrane is measured using a spiral micrometer.
[0118] In addition, in the following examples and comparative examples:
[0119] Branched polyethyleneimine (weight average molecular weight of 25000 g / mol), polyethylene polyamine, 1,4-diaminopiperazine, 1,4-cyclohexanediamine, 1,4-phenylene diisocyanate, cyanuric chloride, 1,3-benzenedisulfonyl chloride, ethyl bromide, propyl chloride, iodomethane, hexyl bromide, hexyl iodide, 1,3-dibromopropane and tetradecane bromide were purchased from J&K Technology Co., Ltd. Other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0120] The support layer is prepared by a phase inversion method, and the specific steps are as follows:
[0121] A certain amount of polysulfone (number average molecular weight of 80000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18 wt%, and degassed at 25°C for 120 min; then, the polysulfone solution was coated on a polyester non-woven fabric (thickness of 75 μm) using a scraper to obtain an initial membrane, which was then immersed in water at a temperature of 25°C for 60 min to allow the polysulfone layer on the surface of the polyester non-woven fabric to undergo phase transformation into a porous membrane, and finally washed with water three times to obtain a bottom layer-porous support layer with a total thickness of 115 μm.
[0122] Example 1
[0123] (1) At 25°C, place the above-mentioned area of 400 cm 2The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the liquid was discharged after contacting for 60 seconds; then the upper surface of the support layer after the first contact was second contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate, and the liquid was discharged after contacting for 60 seconds; finally, the membrane after the two contacts was placed in an oven and heated at 70° C. for 3 minutes to obtain a composite nanofiltration membrane A1;
[0124] (2) At 25°C, the obtained composite nanofiltration membrane A1 was immersed in 200 mL of a methanol solution containing 10 wt% ethyl bromide and 0.5 wt% potassium hydroxide (the weight ratio of ethyl bromide to potassium hydroxide was 20:1) for a third contact, taken out after 5 minutes, and dried at 70°C for 5 minutes to obtain an acid- and alkali-resistant positively charged composite nanofiltration membrane N1.
[0125] from Figure 1 From the XPS spectrum of the surface nitrogen atoms of the acid- and alkali-resistant positively charged composite nanofiltration membrane, it can be seen that a new signal peak appears at 402.4 eV, which corresponds to the signal of the quaternary ammonium salt nitrogen atom, proving that ethyl bromide reacts with the tertiary amine in the acid- and alkali-resistant separation layer to form a quaternary ammonium salt structure.
[0126] Example 2
[0127] (1) At 25°C, place the above-mentioned area of 400 cm 2 The upper surface of the polysulfone support layer is contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethylene polyamine for the first contact, and the liquid is discharged after the contact for 60 seconds; then the upper surface of the support layer after the first contact is contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate for the second contact, and the liquid is discharged after the contact for 60 seconds; finally, the membrane after the two contacts is placed in an oven and heated at 70° C. for 3 minutes to obtain a composite nanofiltration membrane A2;
[0128] (2) At 25°C, the obtained composite nanofiltration membrane A2 was immersed in 200 mL of a methanol solution containing 5 wt% of chloropropane and 0.5 wt% of potassium hydroxide (the weight ratio of chloropropane to potassium hydroxide was 10:1) for a third contact, taken out after 5 minutes, and dried at 70°C for 5 minutes to obtain an acid- and alkali-resistant positively charged composite nanofiltration membrane N2.
[0129] Example 3
[0130] (1) At 25°C, place the above-mentioned area of 400 cm 2The upper surface of the polysulfone support layer is first contacted with 50 mL of an aqueous solution containing 0.5 wt% of 1,4-diaminopiperazine, and the liquid is discharged after contacting for 60 seconds; then the upper surface of the support layer after the first contact is secondly contacted with 30 mL of an Isopar E solution containing 0.1 wt% of 1,4-phenylene diisocyanate, and the liquid is discharged after contacting for 60 seconds; finally, the membrane after the two contacts is placed in an oven and heated at 70° C. for 3 minutes to obtain a composite nanofiltration membrane A3;
[0131] (2) At 25°C, the obtained composite nanofiltration membrane A3 was immersed in 80 mL of a methanol solution containing 10 wt% methyl iodide and 0.5 wt% potassium hydroxide (the weight ratio of methyl iodide to potassium hydroxide was 20:1) for a third contact, taken out after 5 minutes, and dried at 70°C for 5 minutes to obtain an acid- and alkali-resistant positively charged composite nanofiltration membrane N3.
[0132] Example 4
[0133] The preparation method is the same as that in Example 1, except that in step (2), "200 mL of 10 wt% bromohexane" is used instead of "200 mL of 10 wt% ethyl bromide" (the weight ratio of bromohexane to potassium hydroxide is 20:1) to obtain acid and alkali resistant positively charged composite nanofiltration membrane N4.
[0134] Example 5
[0135] The preparation method is the same as that in Example 1, except that in step (2), "200 mL of 10 wt% iodine hexane" is used to replace "200 mL of 10 wt% bromoethane" (the weight ratio of iodine hexane to potassium hydroxide is 20:1) to obtain acid and alkali resistant positively charged composite nanofiltration membrane N5.
[0136] Example 6
[0137] (1) At 25°C, place the above-mentioned area of 400 cm 2 The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid was discharged after contacting for 60 seconds; then the upper surface of the support layer after the first contact was second contacted with 30 mL of an Isopar E solution containing 0.05 wt% cyanuric chloride, and the liquid was discharged after contacting for 60 seconds, and finally the membrane after the two contacts was placed in an oven and heated at 70° C. for 3 minutes to obtain a composite nanofiltration membrane A6;
[0138] (2) At 25°C, the obtained composite nanofiltration membrane A6 was immersed in 200 mL of a methanol solution containing 10 wt% ethyl bromide and 0.5 wt% potassium hydroxide (the weight ratio of ethyl bromide to potassium hydroxide was 20:1) for a third contact, taken out after 5 minutes, and dried at 70°C for 5 minutes to obtain an acid- and alkali-resistant positively charged composite nanofiltration membrane N6.
[0139] Example 7
[0140] (1) At 25°C, place the above-mentioned area of 400 cm 2 The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid was discharged after contacting for 60 seconds; then the upper surface of the support layer after the first contact was second contacted with 30 mL of an Isopar E solution containing 0.2 wt% 1,3-benzenedisulfonyl chloride, and the liquid was discharged after contacting for 60 seconds; finally, the membrane after the two contacts was placed in an oven and heated at 70° C. for 3 minutes to obtain a composite nanofiltration membrane A7;
[0141] (2) At 25°C, the obtained composite nanofiltration membrane A7 was immersed in 200 mL of a methanol solution containing 10 wt% ethyl bromide and 0.5 wt% potassium hydroxide (the weight ratio of ethyl bromide to potassium hydroxide was 20:1) for a third contact, taken out after 5 minutes, and dried at 70°C for 5 minutes to obtain an acid- and alkali-resistant positively charged composite nanofiltration membrane N7.
[0142] Example 8
[0143] The preparation method is the same as that in Example 1, except that in step (2), "200 mL of a mixed solution containing 5 wt% ethyl bromide and 5 wt% 1,3-dibromopropane" is used to replace "200 mL of a solution containing 10 wt% ethyl bromide" (the ratio of the total weight of ethyl bromide to 1,3-dibromopropane and the weight of potassium hydroxide is 20:1) to obtain an acid- and alkali-resistant positively charged composite nanofiltration membrane N8.
[0144] Example 9
[0145] The preparation method is the same as that in Example 1, except that in step (2), "200 mL of 15 wt % ethyl bromide" is used instead of "200 mL of 10 wt % ethyl bromide" to prepare the acid and alkali resistant positively charged composite nanofiltration membrane N9.
[0146] Example 10
[0147] The preparation method is the same as that in Example 1, except that in step (2), "200 mL of 25 wt % ethyl bromide" is used instead of "200 mL of 10 wt % ethyl bromide" to prepare the acid- and alkali-resistant positively charged composite nanofiltration membrane N10.
[0148] Embodiment 11
[0149] The preparation method is the same as that of Example 1, except that in step (2), "take out after 0.5 min" is used instead of "take out after 5 min", to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane N11.
[0150] Example 12
[0151] The preparation method is the same as that of Example 1, except that in step (2), "80 mL of potassium hydroxide containing 0.01 wt %" is used instead of "80 mL of potassium hydroxide containing 10 wt %" to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane N12.
[0152] Example 13
[0153] The preparation method is the same as that of Example 1, except that in step (2), "80 mL of potassium hydroxide containing 0.005 wt %" is used instead of "80 mL of potassium hydroxide containing 10 wt %" to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane N13.
[0154] Embodiment 14
[0155] The preparation method is the same as that of Example 1, except that in step (1), "50 mL of 0.5 wt % 1,4-cyclohexanediamine" is used instead of "50 mL of 0.5 wt % polyethyleneimine" to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane N14.
[0156] Embodiment 15
[0157] The preparation method is the same as that of Example 1, except that in step (2), "200 mL of tetradecane containing 10 wt % bromide" is used instead of "200 mL of ethyl bromide containing 10 wt %" to prepare the acid- and alkali-resistant positively charged composite nanofiltration membrane N15.
[0158] Comparative Example 1
[0159] At 25°C, the above area of 400cm 2 The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine, and the liquid was discharged after contacting for 60 seconds; then, the upper surface of the support layer after the first contact was secondly contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate, and the liquid was discharged after contacting for 60 seconds; finally, the membrane after the two contacts was placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane D1.
[0160] Comparative Example 2
[0161] At 25°C, the above area of 400cm 2 The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethylene polyamine, and the liquid was discharged after 60 seconds of contact; then, the upper surface of the support layer after the first contact was secondly contacted with 30 mL of an Isopar E solution containing 0.1 wt% 1,4-phenylene diisocyanate, and the liquid was discharged after 60 seconds; finally, the membrane after the two contacts was placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane D2.
[0162] Comparative Example 3
[0163] At 25°C, the above area of 400cm 2 The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid was discharged after 60 seconds of contact; then, the upper surface of the support layer after the first contact was secondly contacted with 30 mL of an Isopar E solution containing 0.05 wt% cyanuric chloride, and the liquid was discharged after 60 seconds; finally, the membrane after the two contacts was placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane D3.
[0164] Comparative Example 4
[0165] At 25°C, the above area of 400cm 2 The upper surface of the polysulfone support layer was first contacted with 50 mL of an aqueous solution containing 2 wt% polyethyleneimine, and the liquid was discharged after contacting at 25°C for 60 seconds; then, the upper surface of the support layer after the first contact was second contacted with 30 mL of an Isopar E solution containing 0.2 wt% 1,3-benzenedisulfonyl chloride, and the liquid was discharged after 60 seconds; finally, the membrane after the two contacts was placed in an oven and heated at 70°C for 3 minutes to obtain a composite membrane D4.
[0166] The thickness, surface Zeta potential, average pore size, nitrogen atom content in the quaternary ammonium salt structure in the acid-base resistant separation layer, and contact angle of the acid-base resistant positively charged composite nanofiltration membrane of the embodiment and the composite membrane of the comparative example are shown in Table 1.
[0167] Table 1
[0168]
[0169] The separation layer refers to an acid- and alkali-resistant separation layer;
[0170] a It refers to the content of nitrogen atoms in the quaternary ammonium salt structure in the acid-base resistant separation layer.
[0171] The acid-base resistant positively charged composite nanofiltration membrane of the embodiment and the composite membrane of the comparative example were loaded into a membrane pool and pre-pressed at 1.5 MPa for 1 h. Then, the water flux, Fe 2+ The retention rate was tested; and the acid-base resistant positively charged composite nanofiltration membrane of the embodiment and the composite membrane of the comparative example were immersed in a 5wt% HCl aqueous solution for 7 days, and then pre-pressed at 1.5MPa for 1h, and then the water flux, Fe 2+ The retention rate was tested and the results are shown in Table 2.
[0172] Table 2
[0173]
[0174] As can be seen from Table 2, under the action of alkaline catalyst, the composite nanofiltration membrane is post-treated with halogenated alkanes to react with the tertiary amine groups in the acid-base resistant separation layer structure to convert them into quaternary ammonium salt groups with positive charges. The enhancement of the positive charge on the membrane surface increases the affinity with divalent Fe 2+ The electrostatic repulsion between the two 2+ The interception rate.
[0175] Comparing Example 6 and Example 7, it can be seen that different types of multi-polar monomers will affect their initial retention rate and initial water flux, so in the present invention, it is beneficial to select acid-base resistant positively charged composite nanofiltration membranes prepared by the same multi-polar monomers for vertical comparison. However, the performance of the acid-base resistant positively charged composite nanofiltration membrane prepared by the example meeting the type of multi-polar monomer is better than that of the comparative example.
[0176] By comparing Example 1, Example 9 and Example 10, it can be seen that the amount of halogenated alkane used can affect the degree of reaction between the halogenated alkane and the tertiary amine group remaining on the acid-base resistant separation layer, and ultimately affect the content of nitrogen atoms in the quaternary ammonium salt structure. When the amount of halogenated alkane used is excessive, the retention rate is basically constant and the growth rate is small, but the water flux will be greatly reduced.
[0177] Comparing Example 1 with Example 11, it can be seen that when the third contact time is too short, the reaction cannot be fully carried out, and the retention rate and water flux both decrease.
[0178] Comparing Example 1, Example 12 and Example 13, it can be seen that the amount of catalyst used can promote the reaction of halogenated alkanes with tertiary amine groups on the surface of the composite nanofiltration membrane to be more complete, thereby improving the retention rate and water flux of the acid- and alkali-resistant positively charged composite nanofiltration membrane.
[0179] Comparing Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that when no halogenated alkane is added, the composite nanofiltration membrane cannot achieve a good retention rate and water flux, and has no use value in an acid / alkaline environment.
[0180] After 7 days of treatment with 5wt% HCl, the acid-base resistant positively charged composite nanofiltration membrane 2+ The changes in the retention rate and water flux of the membrane are not obvious, indicating that the acid-alkali resistant positively charged composite nanofiltration membrane has good acid / alkali resistance. Therefore, the positively charged composite membrane can achieve the concentration of divalent and high-valent ions and high H under acidic conditions. + Permeability, high H + The permeability shows that the acid can pass through the acid- and alkali-resistant positively charged composite nanofiltration membrane, and the acid solution can be recycled and reused.
[0181] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An acid- and alkali-resistant positively charged composite nanofiltration membrane, characterized in that: The acid-base resistant positively charged composite nanofiltration membrane comprises a bottom layer, a porous support layer and an acid-base resistant separation layer stacked in sequence; Wherein, the acid-base resistant separation layer contains a quaternary ammonium salt structure.
2. The acid- and alkali-resistant positively charged composite nanofiltration membrane according to claim 1, wherein: The quaternary ammonium salt structure comprises the structural formula shown in Formula I and / or the structural formula shown in Formula II, X is a halogen; n is an integer of 0-10; m is an integer of 2-10; Preferably, X is Cl, Br or I; Preferably, n is an integer of 0-7; m is an integer of 2-8; Preferably, the acid-base resistant separation layer is selected from at least one of a polyurea separation layer, a polytriazineamine separation layer, a polysulfonamide separation layer, a poly(triazineamine-urea) separation layer, a poly(sulfonamide-urea) separation layer, a poly(triazineamine-sulfonamide) separation layer and a poly(triazineamine-sulfonamide-urea) separation layer, preferably selected from at least one of a polyurea separation layer, a polytriazineamine separation layer and a polysulfonamide separation layer.
3. The acid-base resistant positively charged composite nanofiltration membrane according to claim 1 or 2, wherein: The content of nitrogen atoms in the quaternary ammonium salt groups in the acid- and alkali-resistant positively charged composite nanofiltration membrane is 0.5-5 at.%, preferably 2-5 at.%.
4. The acid- and alkali-resistant positively charged composite nanofiltration membrane according to any one of claims 1 to 3, wherein: The surface Zeta potential of the acid-base resistant positively charged composite nanofiltration membrane is 0-30 mV, preferably 5-20 mV.
5. The acid- and alkali-resistant positively charged composite nanofiltration membrane according to any one of claims 1 to 4, wherein: The average pore size of the acid-base resistant positively charged composite nanofiltration membrane is 0.1-0.5 nm, preferably 0.15-0.3 nm.
6. The acid-base resistant positively charged composite nanofiltration membrane according to any one of claims 1 to 5, wherein: The contact angle of the acid-base resistant positively charged composite nanofiltration membrane is 20-80°, preferably 30°-60°.
7. The acid-base resistant positively charged composite nanofiltration membrane according to any one of claims 1 to 6, wherein: The thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; Preferably, the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; Preferably, the thickness of the acid-base resistant separation layer is 10-500 nm, preferably 50-300 nm.
8. A method for preparing an acid- and alkali-resistant positively charged composite nanofiltration membrane, characterized in that: The preparation method comprises the following steps: S1, preparing a porous supporting layer on the bottom layer; S2, the membrane layer obtained in step S1 is first contacted with an aqueous phase containing a polyamine having a tertiary amine group, and is second contacted with an organic phase containing a polyamine having a polar monomer, and after heat treatment, a composite nanofiltration membrane including an acid-base resistant separation layer is obtained; S3, bringing the composite nanofiltration membrane into a third contact with an organic solution containing halogenated alkanes and a catalyst, and drying to obtain the acid- and alkali-resistant positively charged composite nanofiltration membrane.
9. The preparation method according to claim 8, wherein: In step S2, the polyamine containing a tertiary amine group is selected from at least one of polyethyleneimine, polyethylene polyamine, 1-aminopiperazine, 1,4-diaminopiperazine, 1,4-piperazine diethylamine and 1,4-bisaminopropylpiperazine, preferably polyethyleneimine and / or polyethylene polyamine; Preferably, in the aqueous phase of the polyamine containing tertiary amine groups, the concentration of the polyamine containing tertiary amine groups is 0.1wt%-10wt%, preferably 0.5wt%-2.5wt%; Preferably, the polyvalent polar monomer is selected from at least one of polyvalent isocyanates, triazine compounds containing at least two C-Cl bonds, and polyvalent sulfonyl chlorides; Preferably, the polyisocyanate is selected from at least one of meta-phenylenediisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, toluene-2,6-diisocyanate, 1,4-phenylenediisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenylenediisocyanate, 3,3'-dichloro-4,4'-diisocyanatebiphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate and 4-chloro-6-methyl meta-phenylenediisocyanate; preferably selected from 1,4-phenylenediisocyanate and / or 1,3-phenylenediisocyanate; Preferably, the triazine compound containing at least two C-Cl bonds is selected from at least one of cyanuric chloride, 2,4-dichloro-1,3,5-triazine, 2,5-dichloro-1,3,5-triazine and 2,4-dichloro-6-phenyl-1,3,5-triazine; preferably cyanuric chloride; Preferably, the polysulfonyl chloride is selected from at least one of 1,3-benzenedisulfonyl chloride, 1,2-benzenedisulfonyl chloride, 1,4-benzenedisulfonyl chloride, 2,4-disulfonyl chloride-mesitylene, biphenyl-4,4'-disulfonyl chloride, 4,5-dichloro-1,3-benzenedisulfonyl chloride, 2,6-naphthalenedisulfonyl chloride, 1,3-naphthalenedisulfonyl chloride, 2,7-naphthalenedisulfonyl chloride, 1,3,5-benzenetrisulfonyl chloride and 1,3,6-naphthalenetrisulfonyl chloride; preferably 1,3-benzenedisulfonyl chloride; Preferably, in the organic phase, the concentration of the multi-polar monomer is 0.01wt%-2wt%, preferably 0.05-1wt%; Preferably, the amount of the aqueous phase of the polyamine containing tertiary amine groups and the organic phase containing the multi-polar monomer is such that the weight ratio of the polyamine containing tertiary amine groups to the multi-polar monomer is 2-200:1, preferably 5-80:1; Preferably, the first contact time is 5-100 s, preferably 10-60 s; Preferably, the second contact time is 10-200s, preferably 20-120s; Preferably, the heat treatment conditions include: heat treatment temperature of 40-150° C., preferably 50-120° C.; heat treatment time of 0.5-10 min, preferably 1-5 min.
10. The preparation method according to claim 8 or 9, wherein: In step S3, the halogenated alkane is selected from the halogenated alkane represented by formula III and / or the halogenated alkane represented by formula IV; X1, X2 and X3 are each independently halogen; n is an integer of 0-10; m is an integer of 2-10; Preferably, X1, X2 and X3 are each independently Cl, Br or I; Preferably, n is an integer of 0-7; m is an integer of 2-8; Preferably, the halogenated alkane is selected from methyl iodide, ethyl iodide, propyl iodide, butyl iodide, pentyl iodide, hexyl iodide, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, cyclooctane iodide, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, 1,7-diiodoheptane, 1,8-diiodooctane, methyl chloride, ethyl chloride, propyl chloride, butyl chloride, pentyl chloride, hexyl chloride, heptane iodide, octane iodide, nonane iodide, cyclopropane iodide, cyclobutane iodide, cyclopentane iodide, cycloheptane iodide, 1,2-diiodoethane, 1,3-diiodopropane, 1,4-diiodobutane, 1,5-diiodopentane, 1,6-diiodohexane, 1,7-diiodoheptane, 1,8-diiodooctane, At least one of dichloroethane, 1,3-dichloropropane, 1,4-dichlorobutane, 1,5-dichloropentane, 1,6-dichlorohexane, 1,7-dichloroheptane, 1,8-dichlorooctane, methyl bromide, ethyl bromide, propyl bromide, butyl bromide, pentane bromide, hexane bromide, heptane bromide, octane bromide, nonane bromide, cyclopropane bromide, cyclobutane bromide, cyclopentane bromide, cycloheptane bromide, cyclooctane bromide, 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, 1,6-dibromohexane, 1,7-dibromoheptane and 1,8-dibromooctane, preferably at least one selected from ethyl bromide, propyl chloride and methyl iodide; Preferably, the catalyst is selected from at least one of sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, potassium tert-butoxide and sodium tert-butoxide, preferably selected from sodium hydroxide and / or sodium tert-butoxide; Preferably, the organic solvent is an alcohol solvent.
11. The preparation method according to any one of claims 8 to 10, wherein: In step S3, in the organic solution, the concentration of the halogenated alkane is 1wt%-20wt%, preferably 5-10wt%; Preferably, in the organic solution, the concentration of the catalyst is 0.01wt%-5wt%, preferably 0.1wt%-1wt%; Preferably, the weight ratio of the halogenated alkane to the catalyst is 2-50:1, preferably 5-30:1; Preferably, the ratio of the volume of the organic solution to the membrane area of the composite nanofiltration membrane is 0.1-1 mL / cm 2 , preferably 0.3-0.5 mL / cm 2 ; Preferably, the conditions of the third contact include: the third contact time is 1-120 min, preferably 5-60 min; Preferably, the drying conditions include: drying temperature of 30-80°C, preferably 40-60°C; drying time of 0.5-5 min, preferably 1-3 min.
12. Acid- and alkali-resistant positively charged composite nanofiltration membrane prepared by the preparation method described in any one of claims 8 to 11.
13. Use of the acid-base resistant positively charged composite nanofiltration membrane according to any one of claims 1 to 7 and 12 in the field of water treatment.
Citation Information
Patent Citations
Positively charged nano-filtration membrane based on tertiary amine type amphiphilic copolymer and preparation method thereof
CN105642129A
Preparation method of novel anti-pollution amphoteric composite nanofiltration membrane
CN111644082A
Acid / alkali-resistant composite nanofiltration membrane as well as preparation method and application thereof
CN113509839A
Acid-resistant composite nanofiltration membrane and preparation method thereof
CN113559728A
Chlorine resistant polyamide composite membrane and method for producing the same
KR1020080078347A